PENGEMBANGAN SISTEM PERSEDIAAN BARANG BERBASIS MULTIUSER DI PT. SAI APPAREL INDUSTRIES SEMARANG - Danang Danang; Fatimah Indrawati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
Based on the implementation of an internship conducted by the author at PT. SAI APPAREL SEMARANG, the authors try to develop a system in accordance with the needs needed, namely by changing the data processing program inventory system (inventory) that is still using a manual system into a computerized inventory processing program (inventory) based on computerized programming language microsoft visual basic. This change aims to adjust the needs. The use of a computerized inventory system (inventory) in a company or office plays an important role. Because with the presence of a computerized system the data taken and made will be more precise and accurate, while the existing system at PT. SAI APPAREL SEMARANG still uses a manual system so reports that will be given to the leaders are slow.